(untitled) (Journal of Pedagogical Inventions and Practices, 2024)
In this article, the concept of inclusive education, its essence, issues of development of inclusive education, legal basis, problems of education of children with special needs, their solutions, available opportunities, views of our great thinkers on this matter, inclusive education issues such as the principles of development, the proper way to work with parents in educational institutions in the introduction of inclusive education are described